Tables & spreads : a go--to guide for beautiful snacks, intimate gatherings and inviting feasts - Westerhausen, Shelly; Worcel, Wyatt (Chronicle Books, 2021)
"This is a cooking and styling guide that shows you how to create beautiful, abundant spreads-for casual dinners or parties--with stunning photography and creative ideas for every occasion"--